2019
DOI: 10.1097/md.0000000000013283
|View full text |Cite|
|
Sign up to set email alerts
|

A case report of successful treatment of necrotizing fasciitis using negative pressure wound therapy

Abstract: Rationale:Necrotizing fasciitis is a destructive tissue infection with rapid progression and high mortality. Thus, it is necessary that high-performance dressings be introduced as possibilities of treatment.Patient concerns:Female patient, 44 years of age, admitted to hospital unit complaining of lesion in the gluteal region and drainage of purulent secretion in large quantity followed by necrosis.Diagnoses:The diagnosis of necrotizing fasciitis was carried out with the computerized tomography examination resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…When NF is suspected or diagnosed, in order to preserve viable skin and achieve hemostasis, promptly surgical removal of all necrotic tissue, including muscle, fascia, and skin is necessary, what we also proved in our case. [11,12] Affected tissues should be carefully resected until only the healthy tissues remain intact. This should be continued daily, as long as the surgical team determines that all necrotic tissues have been removed.…”
Section: Discussionmentioning
confidence: 99%
“…When NF is suspected or diagnosed, in order to preserve viable skin and achieve hemostasis, promptly surgical removal of all necrotic tissue, including muscle, fascia, and skin is necessary, what we also proved in our case. [11,12] Affected tissues should be carefully resected until only the healthy tissues remain intact. This should be continued daily, as long as the surgical team determines that all necrotic tissues have been removed.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of NPWT include persistent and complete drainage, effective infection control, reduced postoperative secondary necrosis, formation of new granulomatous tissue, and significant short-term improvement in wound status. [31][32][33] Some researchers have also suggested that NPWT reduces the incidence of septic shock, and organ failure. 31,34,35 Clinical diagnosis is particularly important in the treatment of NF, and a comprehensive diagnosis should be made in conjunction with the results of laboratory tests.…”
Section: Discussionmentioning
confidence: 99%
“…It is aimed at the removal of all the necrotic tissues, which include muscle, fascia, and skin, to preserve the viable skin. 13 A combination of surgical debridement, appropriate antibiotics, and optimal oxygenation of the infected tissues is necessary for the successful treatment of the condition. Broad-spectrum antibiotic combinations against anaerobic, gram-negative, and gram-positive bacilli are to be administered in the patient.…”
Section: Discussionmentioning
confidence: 99%